2007
DOI: 10.1007/s10708-007-9049-0
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion of ICT in France: infrastructures, services, and uses

Abstract: How does the organization of space interfere in the numerical development of territories? Our hypothesis is that information and communication technologies (ICT) are organized by taking into account the existing spatial structures, compared to constraints of distance, spatial position and urban hierarchy. In the context of the liberalization of the sector of telecommunications, ICT spread according to an economic logic of profitability. The concern of network operators collides with the principle of territoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The urban-rural disparities described above can largely be explained by the market driven nature of broadband development. Long distances and low population density mean that, in many rural and sparsely populated areas, the demand is insufficient to recoup the cost of the infrastructure investment and thus broadband providers struggle to make a business case for rural expansion (Houzet, 2007;OECD, 2017). The 'last mile' of coverage is generally the most challenging (see Box 1), but it often affects those remote areas for whom digital access could be most transformative.…”
Section: A Municipal Perspective On Broadband Coveragementioning
confidence: 99%
“…The urban-rural disparities described above can largely be explained by the market driven nature of broadband development. Long distances and low population density mean that, in many rural and sparsely populated areas, the demand is insufficient to recoup the cost of the infrastructure investment and thus broadband providers struggle to make a business case for rural expansion (Houzet, 2007;OECD, 2017). The 'last mile' of coverage is generally the most challenging (see Box 1), but it often affects those remote areas for whom digital access could be most transformative.…”
Section: A Municipal Perspective On Broadband Coveragementioning
confidence: 99%
“…Moreover, Daveri and Mascotto (2006) found that in the U.S., only 13 states are highly specialised in IT production. As far as European countries are concerned, the territorial distribution of French ICT firms is an urban phenomenon (Houzet 2007), while in Germany does not seem to possess clusters of IT employment (Frank and Maurseth 2009). In sum, for the Italian case, the concentration of IT industry is less evident than in the U.S. or France.…”
Section: Mappingmentioning
confidence: 99%
“…The flow of information on the Web has been described in papers published by Barnett, Chon and Rosen (2001), Castells (2001), and Ilnicki and Janc (2009). Infrastructural analyses of the Web have been conducted by authors such as Gorman and Malecki (2000), Grubesic and O'Kelly (2002), Malecki (2002) and Houzet (2007). Another significant thread in spatial research on the Web is the analysis of users' social and demographic structure (Warf, 2001;Schwanen & Kwan, 2008).…”
Section: Introductionmentioning
confidence: 99%